SIMULTANEUS INTRAUTERINE AND EXTRAUTERINE PREGNANCY - Stojanoska, Simona; Krste, Stojanoski; Boro, Ilievski; Liljana, Spasevska (Journal of Morphological Sciences; Vol 2 No 1 (2019): JMS, 2019)
Aim: The aim of this report is to present a rare case of early recognized intrauterine and extrauterine pregnancy where pathohistological determination of extrauterine pregnancy in a patient was confirmed. Case report: Patient as an emergency case, in a shock condition was taken to hospital in view of acute abdomen, hypotension with heardly measurable pressure, an accelerated pulse that is difficult to palpate, and severe anemia. Emergency laparatomy confirmed that the patient had an extrauterine ruptured tubal pregnancy. Salpingectomy was performed and the intrauterine pregnancy was allawed to contiunue. Pathohystological finding confirmed the tubal pregnancy. She was given 700 ml of blood transfusion. Intrauterine pregnancy neatly passed with the birth of a live child. Conclusion: Heterotopic pregnancy can occur in the absence of any predisposing risk factors, and the detection of an intrauterine pregnancy does not exclude the possibility of the simultaneous existence of an ectopic pregnancy.  The pathohistological confirmation of the operative material from the salpinghectomy that it is a tubal pregnancy confirmed the suspicion that it is a simultaneus extrauterine and intrauterine pregnancy. Key words : pregnancy, ectopic pregnancy, diagnosis, pathohistological finding